Factors Predicting Financial Sustainability in the Banking Sector - M. Sienly Veronica; Ida Ida; Dimas Peteriandi (Signifikan: Jurnal Ilmu Ekonomi, 2022)
The banking sectors are striving to operate their businesses during the Covid-19 pandemic. This requires innovation to enable the provision of services to the community and improve financial performance. Therefore, this research aimed to analyze the effect of intellectual capital on financial sustainability mediated by financial performance. The purposive sampling technique was employed, with 31 national private banks listed on the IDX as samples and PLS-SEM to solve the research hypothesis. The result demonstrated that the financial performance variable mediates the effect of intellectual capital on financial sustainability. The implication is that the banking sector should pay attention to its intellectual capital, which will improve its financial performance and promote the sustainability of the business.How to Cite:Veronica, M. S., Ida, I. & Peteriandi, D. (2022). Factors Predicting Financial Sustainability in the Banking Sector. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 355-370. https://doi.org/10.15408/sjie.v11i1.25813.JEL Classification: F65, H72, O43, Q01